The effects of dual task training on the neurophysiological parameters in cardiac surgery patients: a pilot study. (14th October 2021) - Tarasova, I; Trubnikova, O; Kukhareva, I; Syrova, I; Sosnina, A; Kupriyanova, D; Nagirnyak, O; Barbarash, O; ,
Abstract: Background: Preventive strategies for postoperative cognitive decline in cardiac patients are being actively developed. The dual task method has demonstrated beneficial potential for treating patients with cognitive impairment. Purpose: To evaluate the effects of dual task training on the neurophysiological parameters in cardiac surgery patients. Methods: 47 patients who underwent elected coronary artery bypass grafting (CABG) or CABG combined with carotid endarterectomy (CEE) were recruited in a prospective study. Patients who did not undergo any cognitive training were assigned to Group 1 (n=21), whereas those who underwent postoperative cognitive training I (postural training and an open-type task) (n=11) and II (visual-motor response and an open-type task) (n=15) were assigned to Group 2 and Group 3, respectively. Cognitive training was carried out daily, starting from the 4th day of the postoperative period. The average number of trainings was 5 for each training group. All patients underwent extensive neuropsychological testing and electroencephalographic (EEG) studies 3–5 days before and 8–11 days after surgery. Results: All patients demonstrated an increase of the theta1 and beta1 EEG rhythms power, an increase in theta/alpha EEG index and a decrease in theta/beta activity index in the early postoperative period of cardiac surgery. Importantly, Group 3 patients undergoing cognitive training II showed an improvement in a larger number of indicators related to executive functions and attention than Group 2 patients undergoing training I. The last reported only improved short-term memory and attention. Conclusion: All patients had similar ischemic brain damage. Those who underwent cognitive training reported improvements in neurodynamics, attention, and memory. The results of the study indicate the need to improve further the approaches to postoperative cognitive training using dual tasks with intensification of the load and individual support for patients undergoing cardiac surgery. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Russian Foundation for Basic Research